A comparative study to assess the effectiveness of iron and folic acid supplementation vs honey dates amla mix on iron deficiency anaemia among adolescent girls residing at the rural orphanage – pilot report - MRS.G. BHUVANESWARI,; MRS. DR. HEPSHIBHA KERUBHAMANI, (International Journal of Pharma and Bio Sciences, 2017)
Anaemia is the most common nutritional deficiency disorder in the world. Iron deficiency anemia is the most common type of anemia and easily treated condition that occurs when there is not enough iron in the body. It is important for girls to increase their consumption of iron-rich foods in rural area such as dates, amla (which is cheaper), red meats, fish, poultry and legumes, to prevent anemia. To determine the effects of iron and folic acid supplementation Vs honey dates amla mix on iron deficiency anemia among adolescent girls in residential home. True experimental research design are selected by simple random sampling technique for one group pre-test and post-test control group design. The study was conducted among 10 adolescent girls in experimental group and 10 in control group at selected residential homes. It shows that, when comparing the level of hemoglobin during pre test in experimental group all 10 samples had severe anemia 10(100%). And in control group also majority 80% of the adolescent girls had a severe anemia, 2 (20%) had moderate anemia. But when comparing the level of hemoglobin during post test in experimental group no one had severe anemia 20 % had mild anemia where as in control group majority 50% adolescence had mild anemia 1(10%) were moderate anemia. The study results reveals that improvement of hemoglobin is very high daily administration of honey dates amla mix comparing to weekly once administration of iron and folic acid supplementation. And also level of satisfaction is high in administration of Honey dates amla mix were comparing to iron and folic acid supplementation.